A Case of Leukemic Retinopathy - Bhattarai, Sarita; Maharjan, Susmina; Shah, Reeya; Shrestha, Anju (International Journal of Silkroad Institute of Research and Training, 2024)
This case report describes a 4-year-old male with a known history of acute leukemia, presenting with blurred vision in both eyes following chemotherapy. On examination, the child exhibited central, steady, and maintained vision, with findings suggestive of leukemic retinopathy, including scattered retinal infiltration, vitreous cells, and exudative retinal detachment in both eyes. Leukemic retinopathy, a rare ocular manifestation of leukemia, often arises from the direct infiltration of leukemic cells and is more commonly seen in acute leukemia. Ocular involvement, which may include retinal hemorrhages, cotton wool spots, and tortuous veins, can serve as an indicator of disease progression and affect prognosis. The patient was managed with topical steroids for vitritis and referred to oncology for systemic reassessment. This case highlights the importance of recognizing ocular involvement in leukemia, as the eye can reveal direct signs of leukemic infiltration and aid in early diagnosis or monitoring of relapse. Close collaboration between ophthalmologists and hematologists is crucial for optimizing patient care and improving both visual and overall outcomes.